Peningkatan Penguasaan Kosakata Bahasa Inggris Siswa Sekolah Dasar Melalui Penggunaan Kamus Bergambar - Mamu, Rahmawaty; Husain, Nurlaila (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This community service aims to improve the English vocabulary mastery of elementary school students at Madrasah Ibtidaiyah Muhammadiyah (MIM) in Gorontalo City through the use of pictorial dictionaries. The implementation method consists of several stages, including needs analysis, pictorial dictionary compilation, implementation in learning, and evaluation. The results of this service show a significant increase in students' vocabulary mastery after using the pictorial dictionary. Observations and interviews with teachers also show an increase in students' motivation and enthusiasm in learning. This success is due to the use of images that help students understand vocabulary in a meaningful context and active student involvement in learning. The impact of this service is not only limited to increasing vocabulary mastery but also in developing innovative learning media. The compiled pictorial dictionary can become a reference for other schools, and the methods used can inspire improving the quality of English language education and other fields.